The Politics Of Education Budgeting Within The Constitutional Framework - Hadi, Muh Sufyan; Rahmatullah, Arwin Yafi (Lentera Ilmu Nusantara, 2025)
Education is a constitutional right guaranteed by the 1945 Constitution of the Republic of Indonesia. Article 31 paragraph (4) mandates the state to allocate at least 20% of the national and regional budgets (APBN and APBD) for the education sector. This study aims to analyze the implementation of this policy in both national and local budgeting practices, and to identify factors affecting the compliance of central and local governments with the constitutional mandate. Using a qualitative approach and descriptive-analytical method, data were obtained through literature review, policy documentation, and case studies in selected provinces. The results indicate that although the central government is relatively consistent in allocating the 20%, issues remain regarding the effectiveness of budget utilization. At the regional level, compliance varies significantly, influenced by fiscal capacity, political commitment, as well as institutional and supervisory constraints. This study recommends strengthening regulations, enhancing public oversight, and providing incentives for local governments to ensure the equitable and just realization of the right to education.